Association of Sublingual Varices With Heart- and Cerebrovascular Disease - Håkan Bergh; Margit Albrektson; Clovis Kastberg; Lennart Hedström (International Dental Journal, 2024)
Objective: The aim of this research was to investigate whether sublingual varices (SV) are associated with new events of ischaemic heart disease (IHD) and new events of cerebrovascular disease. Methods: A prospective observational study was conducted amongst 1139 dental patients aged between 48 and 84 years across 2 cohorts (201 enrolled from 2010–2013 and 938 from 2018–2020). Participants provided baseline data on demographics, risk factors, and medical diagnoses, followed by an assessment of their tongue's ventral surface to classify veins as either having no sublingual varices (nSV) or having sublingual varices (SV). Information regarding medical diagnoses was gathered during the follow-up period from both participants and their medical records. The primary outcome variables were the onset of new IHD and new cerebrovascular disease events. Comparisons were made between participants with SV and nSV. Results: The study population comprised 54% women with an average age of 66 years. SV were present in 33% of participants. Those with SV predominantly were male, older, and smokers; had a higher body mass index, and exhibited more instances of hypertension, diabetes, and dyslipidaemia than those with nSV. New occurrences of IHD (4.5% vs 1.8%, P = .009) and cerebrovascular disease (4.2% vs 2.0%, P = .026) were more prevalent in the SV group compared with the nSV group. The link between SV and new IHD events persisted even after adjustments for sex, age, and smoking habits (OR, 2.26; 95% CI, 1.074.76), but not for new cerebrovascular disease events (OR, 1.77; 95% CI, 0.843.71). Conclusions: Our study identifies a correlation between SV and new events of IHD, but not new events of cerebrovascular disease. The detection of SV occurred prior to the IHD events, suggesting a temporal relationship. This novel finding proposes a potential shared pathophysiology between IHD and SV.